Propose the new executive project manager from BUCG-ABC JV for the construction of BRACU new campus project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the proposal of the new executive project manager from BUCG-ABC JV for the construction of BRACU new campus project.